السياسة الحقوقية: دراسة في دلالات المصطلح - رداوي, عبد المالك; بونوة, نادية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
لم تنل قضية ما اهتماما كبيراً على الساحة الدولية في وقتنا الراهن مثلما حظيت به قضية حقوق الإنسان، التي باتت على سلم أولويات الدول والمنظمات الدولية العامة منها والمتخصصة، وهذا ما جعل من مسألة حماية وترقية حقوق الإنسان مسألة جوهرية وذات أهمية قصوى بالنسبة للدول المختلفة، والتي تستوجب توفير الضمانات والآليات الملائمة التي تسمح لكافة المواطنين -فرادى وجماعات- التمتع بها وممارستها على أرض الواقع خاصة وأن مجرد النص على حقوق الإنسان في المنظومة الدستورية وغيرها النصوص القانونية والتشريعية لا يعني التمتع بها فعليا على أرض الواقع، وليس أفضل من ذلك تجسيدها من خلال سياسة عامة اصطلح على تسميتها بالسياسة الحقوقية، وهذا ما تحاول هذه المقالة الوقوف عنده من خلال الإشارة إلى المقصود بالسياسة الحقوقية وخصائصها ومضمونها بما تتضمنه من ضمانات وآليات وإجراءات. Abstract: The issue of human rights receives a great attention on the international scene. It occupies an advanced position in the scale of states and international organizations priorities, this is what made the protection and the promotion of human rights a fundamental issue worldwide. Therefore, it is necessary to provide adequate guarantees and mechanisms that allow all citizens - individually and collectively - to enjoy their rights and exercise them concretely, so that the stipulation of human rights in the constitutional system and other legal texts does not remain mere ink on paper. This goal falls within the human rights policy, which is what this article tries to explore by referring to what is meant by the human rights policy, its characteristics, contents, and what it includes in terms of guarantees, mechanisms and procedures.